Expression pattern of cancer-associated cellular senescence genes in clear cell renal cell carcinoma distinguishes tumor subclasses with clinical implications - Zhongxu Zhu; Qi Cao; Jingyue Chen; Yiyang Sun; Fang Liu; Jiang Li; Miaomiao Tan (Scientific Reports)
Abstract Clear cell renal cell carcinoma (ccRCC) is a highly lethal subtype of renal cancer. Accumulating evidence suggests cellular senescence impacts tumor development and progression. This study aimed to identify ccRCC subtypes based on a cellular senescence gene signature and assess their clinical relevance. Using hierarchical clustering on the TCGA-KIRC dataset, two senescence-related subtypes were identified and validated in independent datasets. These subtypes exhibited distinct dysregulation of cancer-related pathways, including the p53 pathway. The C2 subtype was associated with poorer overall survival, higher tumor grade and stage, low hemoglobin, and elevated platelet and serum calcium levels. Patients with the C2 subtype also had lower endothelial cell infiltration, indicating reduced benefit from anti-PD-1 immunotherapy. A nomogram based on these subtypes effectively predicted 1-, 3-, and 5-year survival outcomes. These findings highlight two distinct senescence-related ccRCC subtypes that correlate with prognosis and therapy response, offering insights for personalized treatment strategies.